Senegal : a unique political geography in Africa - (:unkn) unknown (My University, 2009)
Long, the area corresponding to the current Senegal enjoys with its opening of the Atlantic Ocean, a remarkable location. The latter has enabled the country to play very early role as a hub in the various trade between Europe, Africa and America. Moreover, until 1960, Dakar is the capital of French West Africa (AOF). In the north, the Senegal River, which gave its name to the country has always been a zone of privileged contact with other African regions. However, since independence in 1960, these indisputable geographical advantages were they valued? To answer this question, we must first examine the demographics of the geopolitics of Senegal, and to question the nature of its internal geopolitical situation. Finally, the question of the two major crises in the Senegal during his first half-century of independence and the reality of its external radiation will be discussed, without forgetting the role of the Senegalese diaspora in the context of globalization.
Keywords: African Research